"Across the Ocean, Across the Tracks": Imagining Global Poverty in Cold War America. (November 2014) - JAHANBANI, SHEYDA
<x content-type="archive" xml:space="preserve">Abstract</x> This article argues that the imagery that American policymakers deployed to represent poverty as a social problem in the United States in the 1960s was rooted in the conceptual vocabulary that had emerged to describe "underdevelopment" in Third World in the years after 1945. Relying upon a close reading of still and moving images produced and distributed under the auspices of the American state in the mid-1960s – including the Academy Award®-winning documentary, A Year Towards Tomorrow – this article explores the ways influential American liberals represented poverty as an explicitly global social problem demanding the intervention of middle-class "agents of change." This moment in the history of poverty fighting marks the origins of the concept of "global poverty."